Experimental and Theoritical Analysis of Thermal Properties in Zephyr Bamboo Tali (Gigantochloa apus Kurz) - Sri Mudiastuti; Armansyah H. Tambunan; Athur Simbolon (PERTETA, 2011)
Abstract Specific heat, thermal conductivity and thermal diffusivity of Bamboo panel are usable to support the Programming of Design and Planning in the Structure of the Agricultural Building Construction. The Specific heat of Bamboo’s fiber, sheet and panel using the method of mixtures varied from 1.585-2.789 J/gr oC, with a mean value of 2.227 J/gr oC in the temperature difference range of 9 ± 0.1oC . It was found it will increase linearly with an increase in the sample temperature. Thermal conductivity values of Bamboo’s fiber based on the transient line heat source technique varied from 0.1035 x 10-3-0.1322 x10-3 J/ cm2 sec oC in the sample temperature 22 to 30 oC on thermal diffusivity of bamboo fiber in 22-30 oC was found to be 0.0823 x 10-3J/cm secoC. The sorption Isotherm and the water activity in the bamboo’s panel is depend on the chemical composition, glue laminated, additive and the porosity. There are related with the absorbing of the water into the bounded water and the diffusivity of the water in and out the panel. The moisture equilibrium range are 7.89 to 19.22 percent in the control of the circumstances and 11 to 75 % of the environment.relative humidity. Keywords: bamboo zephyr, thermal properties, sorption isothermal Abstrak Kapasitas panas jenis, konduktivitas dan difusivitas ernal panel bambu dapat digunakan untuk mendukung Program Desain dan Perencanaan pada Struktur Bangunan dan Gedung dibidang pertanian. Kapasitas panas jenis, pada panel dan papan sera bambu dengan menggunakan metode campuran bervariasi 1,585-2,789 /gr J 0C, dengan nilai rata-rata 2,227 J/gr 0C pada rentang perbedaan suhu 9 ± 0.1 0C. Ditemukan akan serat bambu yang berbasis pada teknik pemanasan transient bervariasi dari 0,1035 x 10-3-0.1322 x 10-3 J/cm2 0C det pada suhu sampel 22-30 OC pada difusivitas termal serat bambu di 22-30 0C ditemukan menjadi 0,0823 x 10-3 J/cm secoC. Penyerapan secara isotermis dan kegiatan aktifitas air pada panel bambu, tergantung pada komposisi kimia, bahan perekat laminasi, aditif dan porositas. Mempunyai kaitan dengan penyerapan air. ke dalam air terikat difusivitas air yang masuk dan keluar panel. Nilai rentang dari keseimbangan kelembaban adalah 7,89 sampai 19,22 persen dalam pengendalian kondisi lingkungan dari 11 sampai 75% dari kelembaban lingkungan. Kata Kunci: Bambu angin sepoi-sepoi, sifat termal, Penyerapan Isotermal Diterima: 13 April 2011; Disetujui: 29 Agustus 2011